STUDENTS’ OPINION ON SUBSTANCE USE, VIOLENT BEHAVIOR AND POSSIBLE INTERVENTION STRATEGIES IN A NIGERIAN PUBLIC UNIVERSITY - Roy J. E. Ndom; David O. Igbokwe; Nduka Ekeruo (European Scientific Journal, ESJ, 2012)
This study investigated students’ opinion on substance use, violent behavior and possible intervention strategies in a Nigerian public university. Two hundred and ninety three participants consisting of 147 males and 146 females with the mean age of 23.67 (SD=3.77) were sampled. A questionnaire designed to elicit student’s opinion on substance use prevalence and proclivity for violent behavior as a result of substance use was administered on the participants using a descriptive cross-sectional research design for data collection. Analysis revealed that majority of the students saw substance abuse as a problem in the university (80.5%), and majority have witnessed violence resulting from substance use (61.4%). Alcohol and marijuana were the top two on the list of substances abused by male and female students and it was reported that violent behaviors like sexual assault, physical assault and violent crimes were common to students after they had abused substance. It was suggested by the respondents that the university authority should use regulation and enlightenment to control substance abuse and use punishment and counseling among others to control violent behavior among students.